THE PATTERN OF TURN TALKING ON VINDES YOUTUBE VIDEO EPISODE NAJWA SHIHAB TERLALU BERANI! VINCENT DESTA YANG TAKUT! - Guspita, Merlina (Kantor Bahasa Maluku Utara, 2023)
This study aims to identify, classify, and analyze speech switching patterns in how to take turns in speaking contained in Vindes' YouTube video episode